TERRITORY, MEMORY AND GENDER: THE MEANINGS OF WOMEN'S POLITICAL PARTICIPATION IN ATENCO, MEXICO - Muñoz,Jacqueline de Lourdes Quintana (2019)
Abstract This paper analyses women´s political participation in the struggle for the protection of the land against the construction of an airport in Atenco, México, between the years 2001-2002. From a gender oriented qualitative approach, the investigation focuses on the characteristics of women´s political participation, social meanings attributed to the process and how they related to their territory. They experienced transformations in their daily lives and gender relations as they got involved in political struggle at two intertwined levels: the dispute with their male partners for their rights as women to participate in the social movement, and the fight for the protection of Atenco´s land.